House dust‐mite allergen exposure is associated with serum specific IgE but not with respiratory outcomes. (7th July 2014) - Bakolis, I.; Heinrich, J.; Zock, J. P.; Norbäck, D.; Svanes, C.; Chen, C. M.; Accordini, S.; Verlato, G.; Olivieri, M.; Jarvis, D.
Abstract: Exposure to house dust has been associated with asthma in adults, and this is commonly interpreted as a direct immunologic response to dust‐mite allergens in those who are IgE sensitized to house dust‐mite. Mattress house dust‐mite concentrations were measured in a population‐based sample of 2890 adults aged between 27 and 56 years living in 22 centers in 10 countries. Generalized linear mixed models were employed to explore the association of respiratory symptoms with house dust‐mite concentrations, adjusting for individual and household confounders. There was no overall association of respiratory outcomes with measured house dust‐mite concentrations, even in those who reported they had symptoms on exposure to dust and those who had physician‐diagnosed asthma. However, there was a positive association of high serum specific IgE levels to HDM (>3.5 kUA /l) with mattress house dust‐mite concentrations and a negative association of sensitization to cat with increasing house dust‐mite concentrations. In conclusion, there was no evidence that respiratory symptoms in adults were associated with exposure to house dust‐mite allergen in the mattress, but an association of house mite with strong sensitization was observed.